2008
DOI: 10.1089/aid.2008.0001
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Disease in HIV Patients Older than 50 Years of Age

Abstract: Our objective was to analyze the prevalence of peripheral arterial disease (PAD) in HIV patients at risk and to compare them with the general population. All HIV patients older than 50 years who attended our unit from October 2005-July 2006 and all persons attending for an annual medical checkup at an employees' insurance association during the same period were invited to participate in the study. Of the latter (n = 407), a person of the same sex and age (+/-5 years) was included for each HIV patient. PAD was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 30 publications
4
23
1
1
Order By: Relevance
“…This is similar to what has been found by others 9 and also may support the contention that the HIV infection-related changes may play a major and independent role in the atherosclerosis process. 29 In this context, the accelerated atherosclerosis process in HIV-infected patients can occur in the absence of detectable viral levels or severe immunodeficiency and has been attributed to a chronic inflammatory state.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is similar to what has been found by others 9 and also may support the contention that the HIV infection-related changes may play a major and independent role in the atherosclerosis process. 29 In this context, the accelerated atherosclerosis process in HIV-infected patients can occur in the absence of detectable viral levels or severe immunodeficiency and has been attributed to a chronic inflammatory state.…”
Section: Discussionsupporting
confidence: 92%
“…11,26 Our main finding supports earlier reports, that HIV-infected patients have a high prevalence of PAD. 9,27 However, our study examined the postexercise changes in the HIV-infected patients who have normal rABI. Thirty (26.5%) of our patients had a significant postexercise drop either in eABI or ASP or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In men participating in the Multicenter AIDS Cohort Study, only paresthesia was associated with older age (47.9% in men older than 50 years compared with 30.6% in younger men; Silverberg et al, 2009). Palacios et al (2008) found that HIVinfected patients had greater prevalence of dyslipidemia, diabetes, and symptomatic peripheral arterial disease as compared with healthy controls.…”
Section: Comorbidities and Age In Persons With Hiv Diseasementioning
confidence: 97%
“…Estudios realizados en España han mostrado una mayor prevalencia de enfermedad arterial periférica diagnosticada por ITB en población VIH respecto a la no infectada 12 . Nos proponemos en este estudio evaluar la utilidad del ITB en una cohorte de pacientes con infección VIH, con vistas a determinar cuántos pacientes son reclasifi cados como de alto riesgo gracias al uso de esta técnica frente a las formas usuales de cálculo de dicho riesgo.…”
unclassified